IMPLEMENTATION OF PRO BONO LEGAL ASSISTANCE FOR JUSTICE SEEKING COMMUNITIES (STUDY AT SUMBER DISTRICT COURT) - Mashuri, Mashuri; Novianto, Saihul; Ramadhan, Dela Putri Intan; Hidayat, Dudung; Faturahman, Dadan Taufik (Ridwan Institute, 2024)
Pro Bono legal aid is a free legal aid program that provides legal aid services both in litigation and non-litigation to underprivileged and marginalized communities in the Sumber Cirebon District Court. The researchers hereby aim to discover the implementation practices and the impediments to effective service delivery, offering valuable information for policymakers, legal practitioners, and organizations dedicated to expanding access to justice for underprivileged communities. The research contributes to both the practical and theoretical understanding of pro bono law aid. It provides a comprehensive analysis of current implementation practices, providing valuable information to policymakers and legal practitioners.